Pengaruh Media Augmented Reality Terhadap Hasil Belajar Siswa Pada Pembelajaran Matematika Kelas V Gugus XI Kota Bengkulu - Sari, Bela Puspita; Agusdianita, Neza; Kurniawati, Ike; Supriatna, Irfan; Yusnia, Yusnia (Universitas Sebelas Maret, 2025)
Students' attitudes and intelligence begin to develop during elementary school. Mathematical resources are one that significantly influences this point in the curriculum. The ultimate goal of mathematics instruction according to BSKAP Decree No. 32 concerning Schools With the help of the 2024 Independent Curriculum, students can understand mathematical ideas by seeing real-world applications. According to Marasabessy et al. (2021), geometry is one of the foundations of mathematics. The purpose of this study was to determine whether the use of Augmented Reality media in grade V students in Cluster XI of Bengkulu City was affected by their mathematics learning outcomes. This study used a quasi-experimental design with a control group design and only involved a pre-test and post-test. Participants in this study were fifth-grade students from Cluster XI of Bengkulu City. Using the Cluster Sampling technique, the researcher selected students from two classes: one, the experimental group from grade VA of SDN 5, and the other, the control group from SDN 41. A total of 10 multiple-choice questions were given as the pre-test and post-test in this study. Students in the experimental and control groups had a t-count of -1.465 and a p-value of 0.0 based on the pre-test data analysis. There was no significant difference in learning outcomes because the Sig. (2-tailed) value of (0.149) was greater than the probability (0.05), the t-table distribution with a significance level of 0.05 was 1.673, and the t-count was smaller than the t-table with a t-count value of -1.465 and a t-table value of 1.673. The post-test data analysis in the experimental and control classes showed that there was a significant difference in the average scores and that Augmented Reality media affected learning outcomes. This was supported by the Sig. (2-tailed) value of 0.000 and the t-table distribution of 1.673, which was smaller than the significance level of 0.05. Therefore, it can be concluded that there was a significant difference in the data and Augmented Reality media affected learning outcomes.Sikap dan kecerdasan siswa mulai berkembang selama sekolah dasar. Sumber daya matematika adalah salah satu yang secara signifikan mempengaruhi titik ini dalam kurikulum. Tujuan akhir instruksi matematika menurut Keputusan BSKAP No. 32 tentang Sekolah Dengan bantuan Kurikulum Independen 2024, siswa dapat memahami ide-ide matematika dengan melihat aplikasi dunia nyata. Menurut Marasabessy et al. (2021), geometri adalah salah satu landasan matematika. Tujuan dari penelitian ini adalah untuk mengetahui apakah siswa kelas V Gugus XI Kota Bengkulu terdampak oleh penggunaan media Augmented Reality pada hasil belajar matematika mereka. Penelitian ini menggunakan desain eksperimen quasy dengan control group design dan hanya melibatkan pre-test dan post test. Peserta dalam penelitian ini adalah siswa kelas lima dari Gugus XI Kota Bengkulu. Dengan menggunakan teknik Cluster Sampling, peneliti memilih siswa dari dua kelas yaitu satu, kelompok eksperimen dari kelas VA SDN 5, dan yang lainnya, kelompok kontrol dari SDN 41. Sebanyak 10 pertanyaan pilihan ganda diberikan sebagai pre-test dan post-test dalam penelitian ini. Siswa dalam kelompok eksperimen dan kontrol memiliki t hitung sebesar -1,465 dan nilai p sebesar 0,0 berdasarkan analisis data pre-test. Tidak ada perbedaan yang signifikan dalam hasil belajar karena nilai Sig. (2-tailed) sebesar (0,149) lebih besar dari probabilitas (0,05), distribusi t tabel dengan tingkat signifikansi 0,05 adalah 1,673, dan t hitung lebih kecil dari t tabel dengan nilai t hitung sebesar -1,465 dan nilai t tabel sebesar 1,673. Analisis data post-test di kelas eksperimen dan kontrol menunjukkan bahwa ada perbedaan yang signifikan dalam nilai rata-rata dan bahwa media Augmented Reality memengaruhi hasil belajar. Hal ini didukung oleh nilai Sig. (2-tailed) sebesar 0,000 dan distribusi t tabel sebesar 1,673, yang lebih kecil dari tingkat signifikansi 0,05. Oleh karena itu, dapat disimpulkan bahwa terdapat perbedaan data yang signifikan dan media Augmented Reality berpengaruh terhadap hasil belajar.